PERLINDUNGAN HUKUM PEMEGANG HAK MEREK VANS OFF THE WALL TERHADAP MEREK VANS OFF THE TOP - Wibisono, Wisesa Adje (JIPRO: Journal of Intellectual Property, 2022)
This study presents an analysis of the legal protection of the holder of the Vans OFF The Wall Brand Rights against the Vans OFF The Top Brand, with the formulation of the problem: What is the form of legal protection for the holders of the Vans OFF The Wall Brand against the Vans OFF The Top brand that is still circulating? and Why is the Vans OFF The Top brand still circulating even though there has been a court decision prohibiting its distribution? This research is a normative research, using secondary data such as laws and regulations, court decisions, and the opinion of scholars. This study obtained the results of legal protection for Vans OFF The Wall Brand holders against Vans OFF The Top which are still in circulation with 2 efforts, namely: Preventive Brand protection leading to preventive actions with the aim of minimizing trademark infringement and Repressive Brand protection aiming to resolve or process events that occur. Furthermore, this study found that one of the reasons the Vans OFF The Top brand is still circulating is that legal protection in Indonesia is weak.